MODEL PENDIDIKAN KEWIRAUSAHAAN BAGI PENGANGGURAN PERKOTAAN PENDUDUK ASLI MISKIN KOTA YOGYAKARTA - Indah Mustikawati (Jurnal Kependidikan, 2010)
This study was aimed at identifying and describing: (1) the growth of entrepreneurship and increasing the skills of poor indigenous people, (2) the effectiveness of entrepreneurship education models in improving the incomes of poor indigenous people, (3) the effectiveness of the model of entrepreneurship education in reducing the number of poor indigenous people in the City of Yogyakarta. This study used the Research and Development design, which consisted of four stages: (1) preliminary study of entrepreneurship education for the community development of urban unemployment in the native residential location of Yogyakarta as an effort to alleviate poverty; (2) preparation of entrepreneurial education model for community urban unemployment;(3) a limited free trial of entrepreneurial education model for community urban unemployment in the city of Yogyakarta, and (4) monitoring. The population represented unemployed people who were the original inhabitants of the City of Yogyakarta. Sampling was conducted using the purposive sampling technique, and selected 33 people consisting of two groups which were in Kecamatan Umbulharjo (Kelurahan Sorosutan, 13 participants) and Kecamatan Tegalrejo (Kelurahan Kricak, 20 participants). Data collection was done using tests, interviews, observation, and documentation. Data analyses used the descriptive, qualitative approach, supported by quantitative data. The results showed: (1) an entrepreneurial education model that was developed to foster entrepreneurship and increase the skills of poor indigenous people was established; (2) the model of entrepreneurship education effectively increased the income of the poor natives by 20% -25%; (3) the model of entrepreneurship education was effective in reducing the number of poor natives